Dual-color emitting Mn2+ ion doped (PEA)2PbBr4 perovskite towards white light-emitting diodes. (25th November 2020) - Gao, Xupeng; Shen, Xinyu; Xue, Dingke; Li, Xin; Lu, Po; Lu, Min; Li, Chunyan; Yu, William W.; Bai, Xue
Abstract : Mn 2+ ion doped 2D (PEA)2 PbBr4 perovskite nanocrystals with a high PLQY of 54% were synthesized using a crystallization method at room temperature, and efficient energy transfer from excitons to the Mn 2+ dopant was proven. Abstract : Two-dimensional (2D) perovskites have become a research hotspot due to their large exciton binding energy and excellent stability. However, it is difficult to achieve longer wavelength emission than blue and green light in the 2D perovskites owing to their wide band gap resulting from their strong quantum confinement. Herein, we demonstrate a simple, efficient and low energy consumption crystallization method at room temperature to synthesize Mn 2+ ion doped 2D (PEA)2 PbBr4 nanocrystals (NCs) with dual-color emission centered at 410 nm from the exciton transition of the host and 600 nm from the d–d transition of Mn 2+ ions. The periodic XRD peaks prove the formation of 2D perovskites. It is reassuring that the high PLQY of 54% has been achieved in the Mn 2+ ion doped 2D (PEA)2 PbBr4 NCs. The temperature-dependent and time-resolved spectra illustrate the efficient energy transfer from excitons to Mn 2+ dopant ions. The realization of white LEDs with different color temperatures presents an opportunity and prospect for Mn 2+ ion doped 2D perovskites in LED application.